2022
DOI: 10.3389/fbioe.2022.870744
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Brewer’s Spent Grain in the Circular Bioeconomy: State of the Art and Future Perspectives

Abstract: Brewer’s spent grain (BSG) accounts for approximately 85% of the total mass of solid by-products in the brewing industry and represents an important secondary raw material of future biorefineries. Currently, the main application of BSG is limited to the feed and food industry. There is a strong need to develop sustainable pretreatment and fractionation processes to obtain BSG hydrolysates that enable efficient biotransformation into biofuels, biomaterials, or biochemicals. This paper aims to provide a comprehe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 117 publications
0
25
0
Order By: Relevance
“…Substrates used in this research had properties similar to those that can be found in the literature (Mainardis et al, 2019;Zeko-Pivač et al, 2022). The pyrolysis temperature is one of the most important parameters (excluding feedstock type) affecting the quality of the produced BC (Zhao et al, 2021).…”
Section: Discussionmentioning
confidence: 80%
“…Substrates used in this research had properties similar to those that can be found in the literature (Mainardis et al, 2019;Zeko-Pivač et al, 2022). The pyrolysis temperature is one of the most important parameters (excluding feedstock type) affecting the quality of the produced BC (Zhao et al, 2021).…”
Section: Discussionmentioning
confidence: 80%
“…Spent grain is a low cost by-product that is available throughout the year, is nutritionally valuable, rich in fiber, proteins and minerals and can be reused in both food and non-food sectors, including animal feed, compost preparations, biogas production, cultivation of microorganisms and production of biomaterials, biochemicals and bricks [ 33 , 37 , 38 ]. Spent grain extract is an approved ingredient in food supplements [ 39 ].…”
Section: Nutritive Value Of Spent Grainsmentioning
confidence: 99%
“…Phenolics in spent grains are associated with the prevention of chronic cardiovascular and neurogenerative diseases, certain cancers and diabetes. The high fiber content helps in the elimination of cholesterol and fats and improves symptoms of ulcerative colitis [ 31 , 33 , 34 , 35 , 36 ]. Reusing spent grain as a value-added food source for human consumption is appealing because it increases the protein, fiber, vitamin and mineral contents while decreasing the starch and caloric content in grain-based products [ 40 ].…”
Section: Nutritive Value Of Spent Grainsmentioning
confidence: 99%
See 2 more Smart Citations